In vivo coronary artery thrombus imaging with 18F-GP1 PET-CT. (14th October 2021) - Tzolos, E; Bing, R; Andrews, J; Macaskill, M; Tavares, A; MacNaught, G; Clarke, T; Williams, M C; Van Beek, E J R; Koglin, N; Stephens, A; Dweck, M R; et al.
Abstract: Background: Coronary artery thrombus is typically present in type 1 myocardial infarction, but small volumes in the setting of an uncertain culprit lesion may be beyond the detection limit of current imaging modalities. Purpose: Using a novel glycoprotein IIb/IIIa-receptor radiotracer, 18F-GP1, we investigated whether positron emission tomography-computed tomography (PET-CT) could detect thrombus formation in coronary arteries. Methods: In a single centre cross-sectional study, patients over 40 years of age with myocardial infarction were recruited after myocardial infarction and underwent underwent CT angiography and 18F-GP1 PET-CT. Stable patients with and without coronary artery disease formed a control cohort. Coronary artery 18F-GP1 uptake was visually assessed and quantified using maximum target-to-background ratios (TBRmax). Results: Ninety-four (44 post-myocardial infarction and 50 control patients) were included in the cross-sectional analysis. The mean age of the post-myocardial infarction group was 61±9 years, three-quarters were male and two thirds had presented with ST elevation on electrocardiography. 34 (80%) patients post-myocardial infarction, but none of the control patients, demonstrated focal 18F-GP1 uptake in the coronary arteries. Of 42 vessels with an angiographic culprit lesion, 35 (83%) had 18F-GP1 uptake which was significantly higher than non-culprit vessels (p<0.0001) as well as control vessels (p<0.0001), while non-culprit vessel uptake was similar to control vessel uptake (p=0.567): culprit vessel median TBRmax 1.2 [interquartile range 0.96–1.44], non-culprit vessel TBRmax 0.96 [0.84–1.03] and control vessel TBRmax 0.9 [0.76 to 0.94]. Linear regression models demonstrated univariable associations between coronary 18F-GP1 TBRmax and time from myocardial infarction, male sex and presence of culprit vessel. On multivariable analysis, only culprit vessel status was associated with TBRmax (adjusted R2= 0.22, P<0.001). Based on the Youden's index of the ROC curves, the optimal cut-off of predicting the presence of a culprit vessel was 1.20 with a specificity of 97%, accuracy of 83%, sensitivity (60%) and c-statictic of 0.74. A patient with ectatic vessel and visual thrombus demonstrated the most intense 18F-GP1 uptake (TBRmax 2.0, highest in the cohort) in the region of heaviest thrombus burden (Figure 2). Extra-coronary uptake was seen in regions of left ventricular thrombus, left atrial appendage thrombus, pulmonary thromboembolism and intramyocardial microvascular obstruction. Conclusions: 18F-GP1 PET-CT is able to detect coronary artery thrombus in culprit lesions following myocardial infarction, as well as extra-coronary thrombotic pathologies that may be important in guiding patient management. 18F-GP1 is highly specific in recognising a culprit lesion from a non-culprit lesion both visually as well as quantitatively. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): British Heart Foundation